Robust backstepping‐based trajectory tracking control for quadrotors with time delays. Issue 12 (1st July 2019) - Liu, Hao; Zhao, Wanbing; Hong, Sheng; Lewis, Frank L.; Yu, Yao
Abstract : In this brief, the robust trajectory tracking control problem is addressed for uncertain quadrotor systems with time delays. The quadrotor dynamical model is an under‐actuated system subject to non‐linearity, unmodelled uncertainties, parametric perturbations, external disturbances, and state and input time delays. A robust cascade trajectory tracking controller is developed by the backstepping method and the robust compensation theory. Theoretical analysis is given to prove that the tracking errors can converge into the given neighbourhood of the origin ultimately. An on‐line unidirectional tuning method is given to determine the controller parameters. Experimental results are provided to verify the effectiveness of the proposed control approach and the parameter tuning method.